GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 341 species occurrences available in GBIF matching the query: TaxonKey: 5725856. The dataset includes 341 records from 33 constituent datasets: 9 records from SysTax - Zoological Collections. 3 records from NPL collections. 2 records from International Fossil Shell Museum (NL) - Mollusca Collection. 43 records from Naturalis Biodiversity Center (NL) - Mollusca. 4 records from Biologiezentrum Linz. 1 records from Marine invertabrate(Mollusca) specimen database of Osaka Museum of Natural History. 4 records from Natural History Museum (London) Collection Specimens. 1 records from Fossil collection (F) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from Recent Invertebrates Specimens. 31 records from Museum of Comparative Zoology, Harvard University. 46 records from invertebratezoology. 4 records from Zoology (Museum of Evolution - Uppsala). 8 records from Collection Malakologie - SNSD. 2 records from Mollusk Collection of Yokosuka City Museum. 8 records from Paleobiology Database. 1 records from Marine Invertebrata specimens deposited in the Fukui City Natural History MUSEUM, Japan.. 1 records from Mollusca collection of National Museum of Nature and Science. 4 records from Bernice P. Bishop Museum. 7 records from NMNH occurrence DwC-A. 11 records from Australian Museum provider for OZCAM. 1 records from Invertebrates Collection of the Swedish Museum of Natural History. 8 records from Queensland Museum provider for OZCAM. 4 records from SOMBASE. 4 records from Invertebrate Zoology Division, Yale Peabody Museum. 1 records from Lund Museum of Zoology (MZLU). 29 records from RBINS collections. 24 records from MAL. 8 records from Molluscs collection (IM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 5 records from University of California Museum of Paleontology. 2 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 51 records from Colección Nacional de Invertebrados - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 1 records from The Paleontological Collections at the Bayerische Staatssammlung für Paläontologie und Geologie. 12 records from Natural History Museum Rotterdam (NL) - Mollusca collection.
Keywords: GBIF; biodiversity; species occurrences